EFEKTIVITAS EDUKASI KONSEP DIRI UNTUK MENINGKATKAN PENGETAHUAN PERKEMBANGAN REMAJA - Yosiana Muftianingrum; Sri Endang Pudjiastuti; Sawab sawab (JENDELA NURSING JOURNAL, 2019)
Background: The role of adolescents will be balanced if the task of adolescent development goes well. Adolescents are required to change their attitudes and behavior in accordance with applicable norms. While a person's behavior is much influenced by his concept. Therefore education about self-concept can be done as a means to help adolescents recognize themselves in the process of development.Purpose: To determine the effectiveness of self-concept education to improve knowledge of adolescent development.Methods: The study used a research design Quasy Experiment with  non randomized contol group pretest posttest. This study uses two groups. The sample of this study is adolescents aged 12-14 years. The sampling technique used is non probability sampling with a purposive sampling method, and consisted of  94 sample / groups. Mann-whitney was conducted to determine the effect of self-concept education in increasing knowledge of adolescent development in the treatment and control groups.Results: Based on the results of the mann-whitney obtained p value = 0.000 (p 0.005), which means that H0 is rejected so that there is an effect of self-concept education on increasing knowledge of adolescent development. Conclusion: Based on the research, it was found that there was a significant effect on the effect of self-concept education on increasing the knowledge of adolescent development in SMP N 21 Semarang. Educating self-concept in early adolescents is expected so that adolescents understand more about the concepts in themselves according to the stage of their development.